2012
DOI: 10.1007/s00261-012-9925-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of somatostatin receptor PET/CT using 68Ga-DOTANOC in gastrinoma patients with negative or equivocal CT findings

Abstract: (68)Ga-DOTANOC PET/CT appears to be useful in patients with gastrinoma with negative or equivocal results on CECT, especially the latter group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…These results might be explained by the previously mentioned difficult interpretations of uptake in the normal pancreatic tissue. In 25 patients with clinically defined gastrinomas with equivocal or negative findings on CT, Naswa et al reported a sensitivity of 68% using 68 Ga-DOTANOC [65].…”
Section: Studymentioning
confidence: 97%
“…These results might be explained by the previously mentioned difficult interpretations of uptake in the normal pancreatic tissue. In 25 patients with clinically defined gastrinomas with equivocal or negative findings on CT, Naswa et al reported a sensitivity of 68% using 68 Ga-DOTANOC [65].…”
Section: Studymentioning
confidence: 97%
“…Using tumor imaging studies in combination with the hypergastrinemia to diagnose ZES, as is increasingly being done in recently reported cases [82, 84, 87, 88, 90, 94, 110, 134] with patients taking or not taking PPIs, has other limitations. In the presence of PPI therapy, one cannot exclude the presence of appropriate hypergastrinemia if a tumor is seen on cross-sectional imaging studies (CT, ultrasound, or MRI), whether the patient has MEN1 syndrome or not and the mass itself may not even be a NET.…”
Section: Proposed Solutions To the Current Controversies In The mentioning
confidence: 99%
“…A high prevalence of somatostatin receptor expression among NETs provides the rationale for peptide receptor-targeted therapy as a treatment modality in patients with inoperable or metastatic disease. The most frequently used radionuclides for targeted radiotherapy in NETs are indium ( 111 In), yttrium ( 90 Y), and lutetium ( 177 Lu), which differs in emitted particles, energy and tissue penetration [52][53]. Both the yttrium-and the lutetium-labeled compounds have demonstrated promising results in patients with NET [54][55].…”
Section: Therapymentioning
confidence: 99%
“…Diagnostic performance of 68 Ga-DOTANOC PET/CT was superior in patients with equivocal ceCT findings than that in patients with negative ceCT. 68 Ga-DOTANOC PET/CT showed more accuracy than ceCT [52].…”
Section: Stagingmentioning
confidence: 99%